Determination of technological parameters of soil compacting process - Basarab, V. A. (Ways to Improve Construction Efficiency, 2020)
The article is devoted to determine the technological parameters of soil compaction by rollers according to soil properties in construction. The compaction of the soil occurs due to certain force loads on the soil. Nowadays, there are enough methods to determine the technological parameters of soil compaction process, however, there are few research methods that consider the system of soil-machine-technological parameters. The urgency of the soil compaction process, which ultimately determines the quality of construction products, was emphasized. The basic physical and mechanical properties of soil and technological parameters of the compaction process were given. Analysis of discrete mathematical model of interaction between roller and soil was carried out in order to determine the technological parameters of soil compaction process in the field of construction technologies. A rheological model to describe the soil properties was used. The differential equations of the interaction between roller and soil have been made. A numerical calculation method to solve the differential equations has been proposed. The basic technological parameters of soil compaction process by rollers have been determined - the thickness of soil layer to be compacted, the number of the roller passes, and the speed of the roller movement. The methodology of theoretical and experimental researches of interaction between roller and soil has been proposed in order to clarify the mathematical model and to find the technological parameters of the compaction process. Experimental research methods are based on the determination of the stress-strain state of soil and on the Fourier analysis of the experimental data. Fourier analysis of the experimental data makes it possible to analyze the qualitative energy spectrum of the interaction between roller and soil to determine the rational amplitude-frequency characteristics of the compaction process. Experimental studies allow obtaining such rheological properties of soil as elasticity, viscosity, coefficient of elastic resistance, etc. The main recommendations for the choice of compaction method depending on the type of soil have been proposed.